ILLNESS BEHAVIOR CONCEPT ANALYSIS: AN APPROACH TO PSYCHOSOCIAL UNDERSTANDING OF HUMAN GETTING ILL - Galán Rodríguez, Antonio; Blanco Picabia, Alfonso; Pérez San Gregorio, Mari Ángeles (Anales de Psicología / Annals of Psychology, 2000)
Illness Behavior concept has let successful approaches to psychosocial understanding of human getting ill but nowadays it is used in a vague and confused way. We have carried out a historial review of this concept, paying specially attention to the ways it has been used. We have also analyzed its conceptual crisis situation and presented the need of delimiting clearly the dimensions that configure it.